Networked Niceness: Gendered Affective Publics and Potentialities of Political Resistance - Harvey, Alison; Bain, Jessica; Whiteman, Natasha; Rambukkana, Nathan (AoIR Selected Papers of Internet Research, 2017)
The contemporary political, economic, and social environment has necessitated a focus within Internet and digital culture studies on the ways in which our platforms, online environments, and shifting digitally-enabled practices can support, perpetuate, and amplify hate, harassment, exclusion, toxicity, and incivility. Within this context, it can be easy to overlook, minimize, or dismiss the spaces and sites where quite the opposite can be observed- the digital enclaves where we find kindness, support, friendship, and the grounds for resistance and organizing. The papers in this panel examine precisely these affective publics via grounded analysis of several sites and practices linked by distinctly different resonances than captured in the focus on online hate. Through critical and qualitative engagement with specific sites of ‘networked niceness’, these papers explore the ways in which such sites are gendered, how they draw on affective relations and discourses as the grounds for feminist activism and resistance, and the ethical questions raised in their research. Through this, they indicate how it is a focus on practices as well as structures that are required in explorations of our digital publics and politics.These papers interrogate the fantasies as well as the potentialities of networked niceness, opening up a conversation about how in a context of online hate we may find the grounds for the next steps in critical engagement and resistance.